2005
DOI: 10.1103/physrevc.71.064601
|View full text |Cite
|
Sign up to set email alerts
|

Local scale transformations and extended matter distributions in nuclei

Abstract: Local scale transformations are made to vary the long range properties of harmonic oscillator orbitals conventionally used in model structure calculations of nuclear systems. The transformations ensure that those oscillator states asymptotically have exponentially decaying forms consistent with chosen single nucleon binding energies, leaving the structure essentially unchanged within the body of the nucleus. Application has been made to the radioactive nuclei 6,8He and 11Li and the resulting wave functions are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
109
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(112 citation statements)
references
References 26 publications
2
109
0
1
Order By: Relevance
“…This new THO basis is obtained by application of a recently proposed LST [33] to the HO basis. The basis obtained provides a suitable discrete representation of the bound and unbound spectrum of a two-body system, which can be used within the CDCC formalism to calculate the scattering observables for reactions involving weakly bound projectiles.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This new THO basis is obtained by application of a recently proposed LST [33] to the HO basis. The basis obtained provides a suitable discrete representation of the bound and unbound spectrum of a two-body system, which can be used within the CDCC formalism to calculate the scattering observables for reactions involving weakly bound projectiles.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the power m, we have found that the results are very weakly dependent on this parameter and, hence, in this work we take m = 4, which is in fact one of the choices used in Ref. [33].…”
Section: The Analytic Lstmentioning
confidence: 99%
See 3 more Smart Citations